La construction sociodiscursive de l'image médiatique de la drag-queen Mado Lamotte : les frontières de la transgression sociale - Laberge, François (Université Laval, 2013)
Selon la perspective interactionniste de la communication développée par Goffman (1973a, 1973b), l’image qu’un individu a de lui-même et qu’il tente de projeter sur les autres se construit au cours de l’interaction en fonction de représentations socialement partagées. Adoptant cette approche théorique, ma recherche vise à identifier, dans les interventions médiatiques de la drag-queen Mado Lamotte, les procédés discursifs qui participent à la construction de son image publique. L’analyse portera sur les actes de parole potentiellement menaçants (Brown et Levinson, 1987) et à leur amplification (Kerbrat-Orecchioni, 1990). Le corpus est constitué de 29 apparitions télévisées principalement extraites d’émissions de divertissement. La méthode d’analyse du discours (Charaudeau et Maingueneau, 2002) a permis de dégager les différents actes de parole menaçants (Venderveken, 1988) ainsi que les types de procédés par amplification (Vincent, Laforest et Turbide, 2008). L’analyse révèle trois dimensions de transgression sociale dans le modèle de construction de l’image de la drag queen : les normes interactionnelles, la frontière entre les domaines public et privé et l’identité de genre.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; analyse de discours; communication; discipline; médias; mémoires/thèses; périodes historiques; québec; régions géographiques; stéréotypes de genre

Cross-dressing to backbeats: An exploration of the practices, wo/men producers, and history of electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; DIG; amériques; approches et analyses; communication; discipline; femmes* artistes; genre; historiographie; montréal; musique; mémoires/thèses; philosophie; point de vue situé; périodes historiques; recherche-création; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail